A comparison of European and US guidelines for familial hypercholesterolaemia. Issue 3 (June 2015) - Reiner, Željko
Abstract : Purpose of review: To compare the European and US guidelines for familial hypercholesterolaemia, but also all the European and US position/consensus papers on heterozygous and homozygous familial hypercholesterolaemia published recently. Recent findings: It has been established that the prevalence of familial hypercholesterolaemia was previously markedly underestimated. The disease is characterized by a lifelong significant increase in LDL cholesterol (LDL-C) levels and therefore premature atherosclerotic cardiovascular disease. Recommendations on familial hypercholesterolaemia have been included as a special chapter in the recent European (European Society of Cardiology/European Atherosclerosis Society) guidelines on dyslipidaemia, whereas in the new US (American College of Cardiology/American Heart Association) lipid guidelines they have been included only generally and these guidelines avoid mentioning familial hypercholesterolaemia explicitly. Both of these guidelines recommend statins in high doses as the treatment option. However, in the American College of Cardiology/American Heart Association guidelines, there is no requirement to attain a specific LDL-C target which is different from the European Society of Cardiology/European Atherosclerosis Society guidelines. Although these two guidelines differ markedly in a number of aspects, they both stress the need to diagnose familial hypercholesterolaemia patients as early as possible and to treat them with intensive LDL-C-lowering therapy. Summary: All the guidelines and consensus papers stress that earlier diagnosis and effective treatment can markedly improve life expectancy among familial hypercholesterolaemia patients.